(untitled) (Research, Society and Development, 2024)
Academic leagues (A.L.) provide students with the opportunity to create educational lectures, recreational programs and projects. The Academic League of Human Anatomy Applied to Dentistry (LAAAO) emerged in 2019, and provides connecting students with activities related to Anatomy aimed at the Dentistry course at Universidade Brasil - Fernandópolis (SP). The objective of the present study was to understand whether there was positive collaboration from A.L. in the student’s academic and personal training, and whether he or she was aware of this collaboration. Research was carried out with a quantitative and qualitative focus. The sample selection was not probabilistic and data collection was carried out using the inquiry technique, through a questionnaire. The results demonstrate that 100% of students who responded to the questionnaire feel closer to the Anatomy subject after joining A.L., in addition, 85.7% of students think that their mastery over the Human Anatomy subject increased after joining. 100% of students agreed that LAAAO helps to improve their academic performance and all participants think that participating in LAAAO can help improve their performance in relation to the curriculum. The data obtained confirm the positive impact of A.L. on connecting students, corroborating the findings of other authors who evaluated this impact on students. We conclude that participation in A.L. contributes positively to academic training, in addition to bringing you closer to the discipline of Human Anatomy. In addition, participating students are aware of this contribution, which contributes to their motivation, increasing learning.